The Effect of Adding Banana Stem Fiber on the Characteristics of Seaweed-Based Bioplastic with Glycerol as a Plasticizer - Hermitha, Ami Diana; Bulkiah, Siti; Subagiyo, Lambang; Nuryadin, Atin (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2026)
The development of biodegradable plastics offers a sustainable alternative to conventional plastics, made using easily degradable materials such as cellulose-containing materials found in seaweed and banana stem fibers. Six tests were conducted, namely tensile testing, absorption testing, biodegradation testing, folding testing, thickness testing, and density testing. The tensile strength test showed the highest value in the seaweed sample at 0.138 MPa. The absorption test indicated that both the seaweed and banana stem fiber samples had lower absorption capacity. The biodegradation test showed that both samples degraded within four days. In the folding test, both types of bioplastics showed excellent flexibility without cracking or tearing. The thickness of the bioplastic increased, with the seaweed-based bioplastic measuring 0.0636 mm and the banana stem fiber-based bioplastic measuring 0.1744 mm. The density of the bioplastic also increased significantly from 120 kg/m³ to 1,200 kg/m³. Based on these results, it can be concluded that the addition of banana stem fiber improves the physical and mechanical properties of bioplastic, making it a potential alternative to environmentally friendly plastic.